DIBUTYLTIN(IV) ALKYLCYCLOHEXYLDITHIOCARBAMATES: SPECTROSCOPIC CHARACTERIZATION AND CRYSTAL STRUCTURES OF DIBUTYLTIN(IV) N-METHYL AND N-ETHYLCYCLOHEXYLDITHIOCARBAMATE - Normah Awang; Ibrahim Baba; Y. Farina Abd. Aziz; Bohari M. Yamin (ASEAN Journal on Science and Technology for Development, 2008)
A new series of dibutyltin(IV) alkylcyclohexyldithiocarbamates of the type (C4H9)2Sn[S2CNR(C6H11)]2 (R = CH3, C2H5, i-C3H7) have been successfully synthesized using in-situ method. These compounds were characterized by elemental analysis, infrared and 13C NMR spectroscopy. A single crystal X-ray analysis of dibutyltin(IV) ethylcyclohexyldithiocarbamate, (C4H9)2Sn[S2CN(C2H5)(C6H11)]2 (compound 2) showed that the system of this crystal is triclinic with space group P-1 while dibutyltin(IV) methylcyclohexyldithiocarbamate, (C4H9)2Sn[S2CN(CH3)(C6H11)]2 (compound 1) has monoclinic system and it’s space group is P21/c. In the crystal structure of compound 2, the dithiocarbamate ligands are bidentically chelated to the tin atom with non-equivalent of the Sn-S distances: Sn(1)-S(1) = 2.9255(11) and Sn(1)-S(2) = 2.5419(10); Sn(1)-S(3) = 2.8922(9) and Sn(1)-S(4) = 2.5293(10) Å while in compound 1, the dithiocarbamate ligands were anisobidentically  chelated to the tin atom.